2010
DOI: 10.2478/v10042-010-0079-y
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin, substance P and calcitonin gene-related peptide-positive intramural nerve structures of the human large intestine affected by carcinoma.

Abstract: Abstract:The aim of this study was to investigate the arrangement and chemical coding of enteric nerve structures in the human large intestine affected by cancer. Tissue samples comprising all layers of the intestinal wall were collected during surgery form both morphologically unchanged and pathologically altered segments of the intestine (n=15), and fixed by immersion in buffered paraformaldehyde solution. The cryostat sections were processed for double-labelling immunofluorescence to study the distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 41 publications
2
37
1
Order By: Relevance
“…The obtained results show that SP-positive neuronal structures are present in all parts of the wall of the porcine descending colon with the exception of the outer muscular layer. SP-like immunoreactivity was observed within neurons and intraganglionic nerve fibers in all kinds of enteric plexuses as well as within nerves in the circular muscular layer and mucosa, what is in accordance with previous studies in various species, including humans [18][19][20][21][22][23][24][25]41,42].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The obtained results show that SP-positive neuronal structures are present in all parts of the wall of the porcine descending colon with the exception of the outer muscular layer. SP-like immunoreactivity was observed within neurons and intraganglionic nerve fibers in all kinds of enteric plexuses as well as within nerves in the circular muscular layer and mucosa, what is in accordance with previous studies in various species, including humans [18][19][20][21][22][23][24][25]41,42].…”
Section: Discussionsupporting
confidence: 92%
“…Till now SP-like immunoreactivity has been observed in various fragments of the GI tract of numerous mammals both in enteric neurons within all types of intramural plexuses, as well as in nerve processes that innervate intestinal muscles and submucosal and mucosal layers [18][19][20][21][22][23][24][25]. SP in the GI tract can play multiple roles according to the species, fragment of the GI tract and type of stimulated receptor .…”
Section: Introductionmentioning
confidence: 99%
“…CGRP, widely expressed in central and peripheral nervous systems, [12] also exerts potent anti-inflammatory effects [13] which may decrease cancer formation [14]. In accordance loss of CGRP expression in human colon cancer was reported [15]. SP is found in both neuronal and extraneuronal cells [16] and we recently demosntrated that SP through neuroimmune modulation decreases breast cancer metastasis and enhances the therapeutic effects of radiotherapy [17].…”
Section: Introductionsupporting
confidence: 62%
“…Moreover, significant interspecies differences in the distribution of enteric neurons immunoreactive to CGRP have been established [32,33,34], which can suggest that exact roles of this peptide are different in various animal species. In contrast, the knowledge concerning the distribution of CGRP in the colonic ENS is relatively scarce and essentially limited to humans and rats [35,36]. It should be pointed out that some similarities between humans [16,33,37] and pigs (this study) have been observed.…”
Section: Discussionmentioning
confidence: 75%